2016
DOI: 10.18203/2394-6040.ijcmph20164724
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of antenatal services in urban slums of Jorhat municipality, Assam, India and the socio - demographic factors affecting it

Abstract: Although efforts have been made to achieve the Millennium Development Goal (MDG) -5 "Improvement of Maternal Health" of reducing the maternal mortality ratio (MMR) by three-quarters by 2015, this goal has not ABSTRACT Background: Antenatal service is an important strategy for improvement of maternal and child health, reduction of maternal mortality and neonatal death. But mere presence of this service is not enough. Utilization of the antenatal service is the most important aspect and there are many socio demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
1
Order By: Relevance
“…8 Study conducted by Singh et al, 23 and Rahman et al, who observed that 24.7% and 19% pregnant females received full antenatal care. 23,27 According to Banerjee, 86%, Javali, 62.6% and Singh et al, 52.5% mother received full ANC services in their study which is higher than that seen in present study. 24,28,29 The difference in utilization of ANC services may be due to variation in awareness health in mothers, availability of health services and health care seeking behaviour of pregnant women.…”
Section: Discussioncontrasting
confidence: 55%
“…8 Study conducted by Singh et al, 23 and Rahman et al, who observed that 24.7% and 19% pregnant females received full antenatal care. 23,27 According to Banerjee, 86%, Javali, 62.6% and Singh et al, 52.5% mother received full ANC services in their study which is higher than that seen in present study. 24,28,29 The difference in utilization of ANC services may be due to variation in awareness health in mothers, availability of health services and health care seeking behaviour of pregnant women.…”
Section: Discussioncontrasting
confidence: 55%